Mengukur Aktivitas Belajar Peserta Didik Melalui Penggunaan Mobile Learning Berbasis Articulate Storyline 3 - Yessi Prihartina; Das Salirawati; Antuni Wiyarsi (Postgraduate, University of Mataram, 2023)
This study aims to measure students' learning activities through the use of articulate storyline 3-based mobile learning with the Project Based Learning learning model on colloidal material. The type of research used is experimental research. The subjects of this study were 17 students of class XI MIPA Negeri 1 Seyegan. The instruments used were question sheets and questionnaire sheets. The indicator of success in this study is the results of student learning activities in general reaching the Active criteria. In research learning activities are carried out with 5 assessments including student worksheet assessment, quiz assessment, poster assessment, presentation assessment, and student activity questionnaire assessment. The results showed that the average student worksheet score was 73.50, the quiz score was 76.46, the poster score was 87.05 the presentation score was 80.60, and the questionnaire score was 76.52. The average value of students from all assessments gets a value of 78.83 and is included in the active category. The recommendation in this study is that the learning activities of students must be further enhanced so that they can provide knowledge to students through direct experiences in learning